2022
DOI: 10.3390/medicina58091261
|View full text |Cite
|
Sign up to set email alerts
|

Post-ERCP Pancreatitis: Prevention, Diagnosis and Management

Abstract: Endoscopic retrograde cholangiopancreatography (ERCP) carries a post-ERCP pancreatitis (PEP) rate of 2–10%, which could be as high as 30–50% in high-risk cases. PEP is severe in up to 5% of cases, with potential for life-threatening complications, including multi-organ failure, peripancreatic fluid collections, and death in up to 1% of cases. The risk of PEP is potentially predictable and may be modified with pharmacological measures and endoscopist technique. This review covers the definition, epidemiology an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
9

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 87 publications
1
24
0
9
Order By: Relevance
“…This study aimed to assess the risk of PEP associated with different canulation techniques. We found the general rate of PEP in our institution to be 9.9%, which was within the previously reported range [1][2][3][4][23][24][25].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This study aimed to assess the risk of PEP associated with different canulation techniques. We found the general rate of PEP in our institution to be 9.9%, which was within the previously reported range [1][2][3][4][23][24][25].…”
Section: Discussionsupporting
confidence: 90%
“…The median age of the subjects was 68 years old (57-76), and there were 119 (51.1%) women. The median body mass index (BMI) was 23 kg/m 2 (21)(22)(23)(24). Periampullary diverticula (PAD) were present in 27 (11.5%) of the cases.…”
Section: Patientsmentioning
confidence: 99%
“…In the study, EUS showed 100% sensitivity, 88.2% specificity while MRCP showed 33.3% sensitivity, 84.6% specificity. [39,40] However, other studies have not found a similar difference and the noninvasive nature of MRCP certainly makes it a preferred option in certain patients who might be at higher risk. [41,42] Given the increasing complexity of therapeutic ERCP procedures and an increasing incidence of PEP noted from 2011 to 2017, thoughtful patient selection is crucial.…”
Section: Preventionmentioning
confidence: 99%
“…Minimally invasive treatments are on the rise because of developments in science and medical technology. A typical treatment is endoscopic retrograde cholangiopancreatography (ERCP) in conjunction with lithotomy [ 5 ]. To start, endoluminal cholangiopancreatography (ERCP) is useful for surgical procedures since it may clearly and comprehensively provide angiographic pictures of the biliary tract.…”
Section: Introductionmentioning
confidence: 99%